Ancient association with Fagaceae in the aphid tribe Greenideini (Hemiptera: Aphididae: Greenideinae). (25th September 2014) - LIU, QING‐HUA; CHEN, JING; HUANG, XIAO‐LEI; JIANG, LI‐YUN; QIAO, GE‐XIA
Abstract Aphids are intimately associated with their host plants. Evolutionary lability of host association is common within heteroecious aphid lineages, whereas our knowledge of host‐use evolution in non‐host‐alternating aphids is limited. In the present study, we construct the first detailed molecular phylogeny of the monoecious aphid tribe Greenideini based on three mitochondrial genes (COI, COII and Cytb) and one nuclear gene (EF‐1α), and investigated its history of host association. Maximum likelihood and Bayesian phylogenies strongly support the monophyly of Greenideini and most constituent genera. Divergence time estimates and character reconstructions suggest that Greenideini may have originated during the Late Cretaceous to early Paleogene, which accompanies the origin of its ancestral host, members of the family Fagaceae. Colonisation of novel host plants has occurred multiple times during the evolutionary history of Greenideini, thereby leading to current patterns of host association. We suggest that directly shifting to novel hosts, together with expanding host range onto pre‐existing, unused plants, has probably promoted diversification in this tribe.